Analisis Perbandingan Efektivitas Iklan Shopee Di Televisi dan Youtube Pada Masyarakat Kota Denpasar - Sihono, Miranda Elfanita; Ras Amanda Gelgel, Ni Made; Ramaswati Purnawan, Ni Luh (E-Jurnal Medium; Vol 4 No 1 (2023): Jurnal Ilmu Komunikasi Vol 4 No 1 Tahun 2023, 2023)
Advertising can be an effective marketing medium to reach the target market. Effective advertising is the kind of advertising that gets the attention of the right target markets to get people to makes purchases or use a product. Shopee became the largest eCommerce brand to spend on television advertising during the January-September 2019 periods. In the meantime, Shopee also uses Youtube as media to advertise. This study aims to compare Shopee advertisements on Television and Youtube in Denpasar City. Non-probability sampling with a purposive sampling method is the sampling techniques that is used in this study. The data in this study were obtained by distributing questionnaires whose results were measured using a Likert scale. This research uses the arithmetic mean analysis technique and T-Test test. The results showed there is differences in effectiveness and stated that Shopee advertisements on Youtube were more effective than Shopee advertisements on television in Denpasar City.